Implementasi Bermain Peran dalam Pengembangan Interaksi Sosial Anak Usia Dini di RA Miftahul Hasanah - Fitria Himatul Aliyah; Dede Nurul Qomariah; Jenal Abidin (Lembaga Penelitian Dan Pengabdian Masyarakat (LPPM) STITNU Al-Farabi Pangandaran, 2026)
Good social interaction can support children in developing communication, empathy, and cooperation skills. One method that can be used to improve children's social interaction is role-playing. Role-playing provides opportunities for children to express themselves, understand other people's feelings, and practice social skills in a safe and supportive environment. This study aims to elaborate on how role-playing is implemented in the development of social interaction in early childhood at RA Miftahul Hasanah. The research was conducted using a qualitative approach with a descriptive method. Data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The results showed that after implementing role-playing twice, there was significant development in the social interaction skills of early childhood at RA Miftahul Hasanah. We found an increase in social interaction development when children who previously had low social interaction skills began to communicate fluently with their friends, were able to cooperate with their friends, and also had a high sense of empathy for their surroundings